Self-reported mask wearing, social distancing and COVID-19 among middle-aged and older Europeans. (20th October 2021) - O'Donovan, MR; O'Caoimh, R
Abstract: Background: Two of the most important recommendations for preventing the spread of COVID-19 are mask wearing and social distancing. This study assesses the prevalence of these behaviors and their cross-sectional association with COVID-19 among middle-aged and older adults in Europe. Methods: This study presents findings from the Survey of Health Aging and Retirement in Europe COVID-19 interviews conducted in 26 European countries in 2020. Frequent mask wearing and social distancing outside the home were categorised as "always" or "often" compared with "sometimes" or "never". COVID-19 status (positive test or hospitalisation) was self-reported. Participants were excluded if they were nursing homes residents, aged <50 years or reported never leaving their home. A further 403 with missing data were removed. SPSS complex samples was used to adjust for survey weights and design. Logistic regression was used to adjust for potential confounding (country of residence, having close contacts with COVID-19 and household size). Results: The sample (n = 40, 647 aged 50-101), with survey weighting, had a mean age of 66 years, 52% were female and 0.8% reported positive for COVID-19. Frequent mask wearing was reported by 82% (range: 2% in Sweden to 99% in Czech Republic), and frequent social distancing by 96% (range: 82% in Slovakia to 99% in Spain). According to unweighted adjusted odds ratios frequent social distancing was associated with lower self-reported COVID-19 (OR: 0.43 95% CI: 0.24-0.76, p = 0.004). Applying survey weighting the adjusted odds ratios were 4.19 (3.07-5.71, p < 0.001) and 0.36 (0.09-1.47, p = 0.156] for mask wearing and social distancing, respectively. Conclusions: The self-reported frequency of adherence to public health recommendations (mask wearing and social distancing) by middle-aged and older Europeans varied significantly between countries in the first year of the pandemic. Social distancing measures may be most effective in this population. Key messages: This large survey found that the frequency of mask wearing and social distancing for adults aged ≥50 varied significantly across 26 European countries in the first year of the pandemic. Frequent self-reported social distancing was cross-sectionally associated with reduced self-reported COVID-19 infection. Further longitudinal research is needed.